A cost-effective method for rapid identification of the southern muriqui (Brachyteles arachnoides): A contribution for the control of illegal bushmeat trade - Valões Cardoso, M. Luiza (2018)
To control illegal wildlife-product trade and protect endangered species of animals, unambiguous identification of the captured specimens is essential. Forensic genetic tools have contributed to identify animal species for conservation purposes promoting accurate results for informing public policies and management of the biodiversity. The southern muriqui (Brachyteles arachnoides) is the largest non-human primate of the Neotropical region and is critically endangered (IUCN Red List of Threatened Species), mainly due to the illegal hunting for bushmeat. In this study, we describe a molecular method using PCR/RFLP to differentiate between bushmeat of southern muriqui and the meat of the domestic animals most commonly consumed in Brazil (Bos taurus, Ovis aries, Capra hircus, and Sus scrofa). The method is based on the amplification and digestion with BanI restriction enzyme of the 16S mtDNA region. We also examine 16S mtDNA sequences of the southern muriqui and other 13 sympatric and parapatric wild species of mammals also hunted for bushmeat to examine whether homologies of the BanI restriction sites could lead to species misidentification. The results indicate the utility of this tool as it represents a simple and cost-effective method to differentiate southern muriqui samples from those of the examined domestic and wild sympatric and parapatric species. We hope this molecular tool will help public authorities in crime prevention, and enhance law reinforcement of illegal hunting of threatened animal species.